PARTISIPASI ORANG TUA DALAM MENINGKATKAN MUTU PENDIDIKAN - Syamsuri Abdurahman, Indra; Cucu Atikah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Parental participation in children's education is a key factor influencing the quality of education in Indonesia. This study aims to explore the differences in parental involvement between urban schools and schools in disadvantaged areas and its impact on education quality. Using a qualitative research method through a literature review of various journal articles published between 2020 and 2024, this study found that parental participation in urban schools is generally higher than in disadvantaged areas. This is due to better access to information, educational resources, and facilities that support parental involvement. On the other hand, parents in disadvantaged areas face significant challenges, including economic limitations, low levels of education, and poor infrastructure, which hinder their ability to participate in their children's education. These findings suggest that improving the quality of education in disadvantaged areas requires interventions focusing on empowering parents and increasing access to educational information and facilities. This research is expected to provide insights for stakeholders in designing programs that support parental participation, thereby reducing educational inequality in Indonesia.